Reading Heidegger - Smythe, Elizabeth (Nursing philosophy, 2020)
Heidegger’s philosophy is a significant contribution to understanding the meaning of lived experience. Recognizing this, nurses and other health professionals have taken on the research approach of Heideggerian hermeneutic phenomenology. This requires reading the writing of Heidegger. Philosophers themselves acknowledge this writing is dense, difficult to grasp, uses language for which there is no easy translation, and leaves the reader with more questions than answers. Drawing on commentary from philosophers who seek to read Heidegger and from a research study which interviewed doctoral students who were "reading Heidegger," we seek to show the nature of the experience of pursuing such a challenging quest.